Friction improvement of palm kernel activated carbon-epoxy by oil and water impregnation - Ibrahim, Maziah (2019)
It has become a whole wide problem that friction and wear causing a huge amount of energy loss. Friction improvement is needed to obtain maximum efficiency and at the same time being environment-friendly by reducing waste. Some study show that 50% of premature bearing failure were due to lubricants. The purpose of this project is to study the improvement of friction by using PKAC composite and to investigate the effect of impregnated time on friction and wear properties of the PKAC .The composite will be impregnated by palm oil, paraffin oil and water for I day and 8 days as solid lubricant since lubricant can reduce friction between surfaces. The result of coefficient of friction and wear rate of PKAC will be taking by using ball-on-disc tribometer. Basically, the composite were formed into disc shaped using hot compaction technique. When the composite were ready, basic mechanical test were done. Then the composite were tested through ball-on-disc tribometer. The results show that the COF of composite impregnated by water and oil are better than COF of un-soaked composite. From the study, it is interesting to find that COF of composite impregnated by palm oil is better than paraffin oil. While wear rate of paraffin oil is better than palm oil. This behaviour shows that the effect of COF and wear is also depend on the temperature, viscosity of lubricants and any others. In addition, the effect of impregnation time are not really significant in friction. The lubricant quickly fully absorb when the composite impregnated for a long time. In conclusion, the result of COF of PKAC impregnated by water and oil were better than the un-soaked composite which is between 0.04 to 0.06 COF. Thus, it can be said that palm oil and paraffin oil can be good impregnated medium for PKAC to improve friction.